Cobalt-catalyzed enantioselective directed C-H alkylation of indole with styrenes - Lee, Pin-Sheng (2015)
A cobalt–chiral phosphoramidite catalyst promotes enantioselective imine-directed C2-alkylation of Boc-protected indoles with styrenes. The reaction affords 1,1-diarylethane products in moderate to good yields with good enantioselectivities under mild conditions. A deuterium-labeling experiment suggests that the enantioselectivity is controlled by both the styrene insertion and the C–C reductive elimination steps.